“O MEDICAMENTO É UMA VÁLVULA DE ESCAPE”: UM ESTUDO SOBRE A DEPRESSÃO NA REGIÃO CENTRO-OESTE DO PARANÁ (2010 – 2017) - Pszdzimirsk, Jéssica Fernanda (2019)
Over the last thirty years, the use of medicines related to mental distress, especially depression, has been increasing in all layers of society. To justify this growth, there are several hypotheses; among them, the model of diagnostic for depression can be stressed. This dissertation presents an analysis of the conditions of possibilities that led depression to be, in a few decades, one of the most diagnosed and medicalized diseases. We will analyze this finding through a documentary survey carried out in public health care services in four cities in the Midwest of Paraná, between 2010 and 2017. Interviews with doctors and patients who take or have taken psychotropic drugs will be discussed. The main objective is to understand how the construction of an epidemic of depression goes through the reorganization of knowledge in different scales, both scientific and popular, as well as general and local. The work was elaborated from perspectives situated in the history of the diseases. To this end, theoretical concepts such as “knowledge” and “power” were used to analyze how these relationships occur and how the control of bodies has been shaped through medicalization. Methodologically, it was necessary to use oral history, scale variation and gender category. We divided the discussion into three main topics: first off, a study of the literature on the subject, as well as the explanation of key concepts for understanding the research. Secondly, starting with a macro scale, we tried to gather international and then national data on the use of psychotropic drugs. Varying the scale, we discussed the issue, problematizing our medicalized region with its quantitative data and also with qualitative sources, using interviews of doctors and users of psychotropic drugs. Thirdly, we discussed the constructions of masculinity and femininity underlying the interviews, aiming to show that the medicalization of society is gendered. Finally, we presented research considerations that will allow us to think about new possibilities and also to understand that nothing is immutable, immovable, defined and limited.